Simulación numérica CFD de la estructura de control y del sistema de compuertas radiales – Represa El Quimbo - Ladino Moreno, Edgar Orlando (Escuela Colombiana de Ingeniería Julio Garavito, 2017)
The general objective of this study is related to the development of a numerical model in 2D without considering the effect of stacks and stirrups in the water, at 1:70 scale, under conditions of permanent flow of control structure and system Of radial gates - El Quimbo Dam, from the implementation of ANSYS Fluent 17.0 software. The hydrodynamic analysis of the structure was performed under free surface conditions with different hydraulic loads (H / HD = 0.5, H / HD = 1, H / HD = 1.33), for different flows (3024 m3 / s, 3312 m3 / S, 4261 m3 / s, 5210 m3 / s, 11,888 m3 / s), and for openings of 704 msnm, 706.9 msnm, 709.4 msnm, 712 msnm and 724.6 msnm. The behavior of the residual values ​​was evaluated until the level of convergence was obtained. In addition, the mesh independence was studied to determine the optimum level of refinement. The inlet and outflow boundary conditions of the flow, the behavior of the water sheet through the landfill, the discharge coefficients, the approach velocities and the variations in the pressure fields developed in the radial gate system , In the fast and in the deflector. Subsequently, the numerical model was validated, based on the comparison of the numerical results with the theoretical data made by INGETEC and the data of the tests carried out in the physical model developed by the National University of Colombia (Manizales site). Finally, the capacity of the numerical model to simulate the hydraulic behavior of the physical model was evaluated, establishing the degree of variation of the real data with the data obtained through the numerical simulation.

El objetivo general de este estudio se relaciona con el desarrollo de un modelo numérico en 2D sin considerar el efecto de las pilas y los estribos en el azud, a escala 1:70, bajo condiciones de flujo permanente de la estructura de control y del sistema de compuertas radiales – Represa El Quimbo, a partir de la implementación el software ANSYS Fluent 17.0. El análisis hidrodinámico de la estructura se realizó bajo condiciones de superficie libre, con diferentes cargas hidráulicas (H/HD= 0.5, H/HD= 1, H/HD= 1.33), para distintos caudales (3024 m3/s, 3312 m3/s, 4261 m3/s, 5210 m3/s, 11,888 m3/s), y para aperturas de 704 msnm, 706.9 msnm, 709.4 msnm, 712 msnm y 724.6 msnm. Se evaluó el comportamiento de los valores residuales hasta obtener el nivel de convergencia. Adicionalmente, se estudió la independencia de la malla para determinar el nivel de refinamiento óptimo. Se analizaron las condiciones de contorno de entrada y de salida del flujo, el comportamiento de la lámina de agua a través del vertedero, los coeficientes de descarga, las velocidades de aproximación y las variaciones en los campos de presión desarrollados en el sistema de compuertas radiales, en la rápida y en el deflector. Posteriormente, se validó el modelo numérico, a partir de la comparación de los resultados numéricos con los datos teóricos realizados por INGETEC y los datos de las pruebas realizadas en el modelo físico desarrollado por la Universidad Nacional de Colombia (sede Manizales). Finalmente, se evaluó la capacidad del modelo numérico para simular el comportamiento hidráulico del modelo físico, estableciendo el grado de variación de los datos reales con los datos obtenidos mediante la simulación numérica.
Keywords: CFD; VOF; Presas; Modelos matemáticos; Depósitos para Agua; Represa El Quimbo; CFD; VOF; Dams; Mathematical Models; Water Storage; El Quimbo Dams